2013
DOI: 10.1016/j.apal.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Polish spaces

Abstract: In the presence of suitable power spaces, compactness of X can be characterized as the singleton {X} being open in the space O(X) of open subsets of X. Equivalently, this means that universal quantification over a compact space preserves open predicates.Using the language of represented spaces, one can make sense of notions such as a Σ 0 2subset of the space of Σ 0 2 -subsets of a given space. This suggests higher-order analogues to compactness: We can, e.g. , investigate the spaces X where {X} is a ∆ 0 2 -sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 55 publications
2
124
0
Order By: Relevance
“…Note that for Polish spaces the class Σ 1 1 of analytic sets has several nice equivalent characterizations (in particular, as the class of continuous images of Polish spaces or as the class of sets obtained from the closed sets by applying the Suslin A-operation). In Lemma 56 of [Bre13] it was observed that the characterization in terms of continuous images extends to the quasi-Polish spaces. In Section 8 we will see that this characterization fails in general for non-countably based admissibly totally represented spaces.…”
Section: Hierarchiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that for Polish spaces the class Σ 1 1 of analytic sets has several nice equivalent characterizations (in particular, as the class of continuous images of Polish spaces or as the class of sets obtained from the closed sets by applying the Suslin A-operation). In Lemma 56 of [Bre13] it was observed that the characterization in terms of continuous images extends to the quasi-Polish spaces. In Section 8 we will see that this characterization fails in general for non-countably based admissibly totally represented spaces.…”
Section: Hierarchiesmentioning
confidence: 99%
“…In [Bre13] the following important characterization of quasi-Polish spaces in terms of Borel hierarchy was obtained. Proposition 3.6.…”
Section: Hierarchiesmentioning
confidence: 99%
See 3 more Smart Citations